2019
DOI: 10.3390/ijerph16091555
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Blastocystis Activity In Vitro of Egyptian Herbal Extracts (Family: Asteraceae) with Emphasis on Artemisia judaica

Abstract: Achillea fragrantissima (Forssk.) Sch. Bip. (known as Qaysoom), Echinops spinosus L. (known as Shoak Elgamal) and Artemisia judaica L. (known Shih Baladi) are members of the Asteraceae family known for their traditional medical use in Egypt. The ethanol extracts of these plants were evaluated for their efficacy against a protozoan parasite (Blastocystis). Two different molecular subtypes of Blastocystis were used (ST1 and ST3). Significant growth inhibition of Blastocystis was observed when exposed to both A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…The vacuolar morphological stage of Blastocystis sp. was prevalent in both symptomatic and asymptomatic patients, as reported in other studies [ 12 ]. No association was found between its morphological stage and gastrointestinal symptom, in contrast to other studies that reported associations with the symptoms.…”
supporting
confidence: 79%
“…The vacuolar morphological stage of Blastocystis sp. was prevalent in both symptomatic and asymptomatic patients, as reported in other studies [ 12 ]. No association was found between its morphological stage and gastrointestinal symptom, in contrast to other studies that reported associations with the symptoms.…”
supporting
confidence: 79%
“…Herbal products can enhance the actions and diminish the toxicity of conventional chemotherapeutic drugs [ 1 ]. Artemisia judaica L. (Arabic name, Shih Balady) belongs to the family Asteraceae and grows widely in the Mediterranean region [ 5 ]. A. judaica L. is widely used by Bedouins as an anthelmintic and antiseptic oil.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific reports have handled the biological activities of the crude extract, fractions of different polarities, isolated active fractions, or pure compounds. The ethanolic crude extract of A. judaica L. has shown anti-blastocystis, antihyperglycemic, antihyperlipidemic, antioxidant, anti-inflammatory, and antiapoptotic effects [ 5 , 12 ]. Additionally, the hydro-methanolic extract of the aerial parts proved its hypoglycemic activity through the inhibition of α -glucosidase and significant scavenging activity for 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Girish et al (2015) reported uniform inhibition among different Blastocystis subtypes. On the contrary, other anti- Blastocystis protease inhibitors induced variable effects on different Blastocystis subtypes ( Al-Mohammed et al, 2013 , Mokhtar et al, 2019 ). Subtype dependent variation might explain the variable response of different Blastocystis subtypes to the same drug in vitro ( Mokhtar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the cultivation interval, culture sediment of each isolate was examined by iodine smear, then the four tubes were divided as follows; three tubes were further sub-cultured for conducting the drug susceptibility assay, while 0.5 ml of the fourth culture tube sediment was frozen at −20 °C for DNA extraction ( Mokhtar et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%